A Putative Mitochondrial Iron Transporter MrsA in Aspergillus fumigatus Plays Important Roles in Azole-, Oxidative Stress Responses and Virulence - Long, Nanbiao; Xu, Xiaoling; Qian, Hui; Zhang, Shizhu; Lu, Ling (Frontiers in Microbiology, 2016)
Iron is an essential nutrient and enzyme co-factor required for a wide range of cellular processes, especially for the function of mitochondria. For the opportunistic fungal pathogen Aspergillus fumigatus, the ability to obtain iron is required for growth and virulence during the infection process. However, knowledge of how mitochondria are involved in iron regulation is still limited. Here, we show that a mitochondrial iron transporter, MrsA, a homolog of yeast Mrs4p, is critical for adaptation to iron-limited or iron-excess conditions in A. fumigatus. Deletion of mrsA leads to disruption of iron homeostasis with a decreased sreA expression, resulted in activated reductive iron assimilation (RIA) and siderophore-mediated iron acquisition (SIA). Furthermore, deletion of mrsA induces hypersusceptibility to azole and oxidative stresses. An assay for cellular ROS content in ΔmrsA combined with rescue from the mrsA-defective phenotype by the antioxidant reagent L-ascorbic acid indicates that the increased sensitivity of ΔmrsA to the azole itraconazole and to oxidative stress is mainly the result of abnormal ROS accumulation. Moreover, site-directed mutation experiments verified that three conserved histidine residues related to iron transport in MrsA are required for responses to oxidative and azole stresses. Importantly, ΔmrsA causes significant attenuation of virulence in an immunocompromised murine model of aspergillosis. Collectively, our results show that the putative mitochondrial iron transporter MrsA plays important roles in azole- and oxidative-stress responses and virulence by regulating the balance of cellular iron in A. fumigatus.